Overview of Resilience in Breast Cancer Women Who Have a Mastectomy - Fitrotul Mahfudhoh, Laili; Retno Surjaningrum, Endang (Rifa'Institute, 2024)
Introduction: Cancer is a non-communicable disease caused by the abnormal and uncontrolled growth of body tissue cells. One of the chronic diseases that is quite often encountered in Indonesia is breast cancer. Breast cancer, also known as Carcinoma Mammae, is a malignant tumor in the form of abnormal growths that appear in breast tissue. Objective: This study aims to analyze how resilience is described in women with breast cancer who undergo mastectomy. To find out, it is necessary to dig up information on the extent of the individual's understanding of the experience that has been passed related to mastectomy. Method: This study uses a qualitative method with a phenomenological approach. Data mining was carried out through interviews with two informants, namely NH and SI who had performed mastectomy. The data analysis technique was carried out using the Interpretative Phenomenological Analysis (IPA) technique. Result and Discussion: The results of this study showed that participants had good resilience in terms of the ability to survive breast cancer diagnosis, treatment, mastectomy to recovery until declared cured. Participants also had good emotional regulation, optimism, causal analysis, empathy, impulse control, self-efficacy and reaching out. Participants were able to respond to the effects arising from mastectomy calmly and wisely because of their interpersonal skills. Conclusion: Participants have self-strength, including strong confidence, positive thinking, and full of sincerity and gratitude in facing challenges towards life resilience.